Do we need you? : The roles of teacher supervisor in embracing Industrial Revolution 4.0 - Adnan, W.I.W.; Wahid, N.A.; Majid, N.A.; Jaafar, F.W.; Ismail, N.A.; Wahab, N.A (2020)
The industrial revolution (IR 4.0) or the Industrial Internet of Things (IIoT) is characterized by the massive expansion of computation, digitalization, networking and physical processes. The so-called Industry . penetrates various industries and life domains by paving its way to the global networking system through data transmission. Thus, the emergence of IR 4.0 may change the dynamic in the teacher supervisor construct. Therefore, this conceptual paper aims to examine the teacher supervisor roles in the era of IR 4.0. Hence, a conceptual framework is proposed to identify critical roles played by teacher supervisor which should be retained in embracing IR 4.0. Findings indicate that supervisor's roles in providing professional conference, encouragement for reflection and emotional support should remain.